Information systems project management - Olson, David Louis (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
Addresses project management in the context of information systems. It deals with general project management principles, with focus on the special characteristics of information systems. It is based on an earlier text, but shortened to focus on essential project management elements.
1. Introduction to project management -- Part I. The human element -- 2. Human factors in information systems project management -- 3. Project organization -- Part II. Project adoption and planning -- 4. Project selection and approval -- 5. System development -- Part III. Tools -- 6. Estimation -- 7. Quantitative project scheduling methods -- Part IV. Project completion -- 8. Project control and assessment -- 9. Project implementation -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF title page (viewed on January 26, 2015).
Keywords: Project management; Information resources management; Management information systems